1985
DOI: 10.1152/ajpgi.1985.249.4.g528
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pentobarbital sodium anesthesia on splanchnic hemodynamics of normal and portal-hypertensive rats

Abstract: To determine the effect of pentobarbital sodium anesthesia on the rat with portal hypertension due to portal vein stenosis, four groups of rats were studied. Cardiac output and regional blood flow were measured by radioactive microspheres in anesthetized and conscious sham-operated and portal-hypertensive rats. Anesthesia markedly decreased cardiac output in both sham-operated (109.7 +/- 4.6 vs. 77.8 +/- 1.4 ml/min, P less than 0.001) and portal-hypertensive rats (130.1 +/- 7.6 vs. 93.8 +/- 5.3 ml/min, P less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 0 publications
0
33
0
Order By: Relevance
“…Conversely, octreotide may induce a vasoconstriction if the drug is given in portal hypertensive rats with a baseline vasodilation. 13 Another peptide, atrial natriuretic peptide, has been shown to elicit either vasodilation or vasoconstriction, depending on the level of the pre-existing vascular tone. 15 In conclusion, octreotide decreased splanchnic and systemic vasoconstriction in portal hypertensive rats pre-treated with terlipressin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, octreotide may induce a vasoconstriction if the drug is given in portal hypertensive rats with a baseline vasodilation. 13 Another peptide, atrial natriuretic peptide, has been shown to elicit either vasodilation or vasoconstriction, depending on the level of the pre-existing vascular tone. 15 In conclusion, octreotide decreased splanchnic and systemic vasoconstriction in portal hypertensive rats pre-treated with terlipressin.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac output and regional blood¯ows were measured by the radioactive microsphere method and the reference sample method as previously described. 12,13 For the ®rst set of haemodynamic measurements a precounted aliquot of » 60 000 16 1 lm diameter, 141 Ce-labelled, microspheres (speci®c activity of 10 lCi/g; New England Nuclear, Boston, MA, USA), suspended in Ficoll 70 (10% Pharmacia; Fine Chemicals AB, Uppsala, Sweden) and Tween-80 (0.01%) and ultrasonically agitated, was injected into the ventricular catheter and¯ushed with 1 mL of isotonic saline for 45 s. During the microsphere injection, a reference blood sample was drawn from the catheter in the femoral artery into a motor-driven syringe at 0.8 mL/ min for 1 min For the second set of haemodynamic measurements 113 Sn-labelled microspheres were injected using the same technique. The animal was then killed with an overdose of pentobarbital sodium.…”
Section: Haemodynamic Measurementsmentioning
confidence: 99%
“…For this, haemodynamic values were measured prior to and 20min after the intracerebroventricular administration (Wright et al, 1986) Haemodynamic studies were performed in conscious unrestrained rats. Cardiac index and regional blood flows were measured by the radioactive microsphere method and the reference sample method as previously described (Lee et al, 1985). For the first set of haemodynamic measurements, a precounted aliquot of approximately 60,000, 16+ 1 I m diameter, "'Ce-labelled microspheres (sp.…”
Section: Protocolsmentioning
confidence: 99%
“…The second group contained 16 rats with portal hypertension induced by the partial ligation of the portal vein, as previously described. 18 The hemodynamic study was performed 2 weeks later, when portal hypertension had fully developed. The third group contained 16 rats with secondary biliary cirrhosis caused by bile duct ligation.…”
mentioning
confidence: 99%